Chthamalus montagui as biomonitor of metal contamination in the northwest coast of Portugal - Pedro A Reis (2012)
The concentrations of seven metals (Cd, Cr, Cu, Fe, Mn, Ni and Zn) were determined in coastal seawaters and soft and hard tissues of the barnacle Chthamalus montagui from the northwest coast of Portugal to assess the potential use of C. montagui as biomonitor of metal contamination. The results of this study showed that C. montagui soft tissues can be used for monitoring metal bioavailabilities in these coastal seawaters: (1) there were significant correlations (p < 0.05) between the metal concentrations in soft tissues and their concentrations in seawaters and (2) barnacle soft tissues were sensitive to spatial variation of metal bioavailabilities, accumulating different amounts of metals in different locations. The range of concentrations in tissues were: 0.59-1.7 mg Cd kg(-1), 0.5-3.2 mg Cr kg(-1), 0.72-3.0 mg Ni kg(-1), 1.2-6.7 mg Cu kg(-1), 9-26 mg Mn kg(-1), 214-785 mg Fe kg(-1) and 178-956 mg Zn kg(-1); (3) mean logarithmic bioaccumulation factors (log BAF) of Fe, Cr and Cd were higher, 5.49, 4.93 and 4.46, respectively, than mean log BAFs of Mn, Zn, Cu and Ni, 4.03, 3.97, 3.74 and 3.61, respectively. In contrary, C. montagui shell plates were not a good matrix to monitor metal bioavailability in these coastal seawaters, with no significant correlations (p < 0.05) between metal concentrations in the shell and in seawater. Regarding the high Zn concentrations obtained in the coastal seawaters and C. montagui soft tissues, all seawaters from northwest coast of Portugal should be classified as "moderately/remarkably polluted".